Pengaruh Perputaran Kas Dan Perputaran Piutang Terhadap Profitabilitas Di Perusahaan Property Dan Real Estate Yang Terdaftar Di BEI Periode Tahun 2018-2022 - Fadillah, Muhamad Rifki; Askolani; Oktaviani, Nita Fauziah (Jurnal Bisnis, Manajemen dan Akuntansi, 2024)
Profitability is an important indicator for assessing a company's financial health and performance.  The aim of this research is to determine the influence of Cash Turnover and Receivables Turnover on Profitability as measured by Return On Assets (ROA) simultaneously or partially.  The data used in this research are the annual financial reports of Property and Real Estate companies listed on the Indonesian Stock Exchange (BEI) for the 2018-2022 period.  The sampling method used was purposive sampling and 15 companies were obtained as samples.  This research uses a quantitative descriptive approach.  The data analysis technique used in this research is panel data regression analysis using E-Views 12. The results of this research can be concluded that Cash Turnover and Receivables Turnover simultaneously have a significant effect on Profitability.  Meanwhile,  Cash Turnover has a insignificant effect on Profitability, and Receivables Turnover has a significant effect on Profitability.